AB1147 Comorbidity profile in men and women affected by syntomatic knee osteoarthritis and impact of gender in the symptomatology and perception of health status. (15th June 2017) - Barbero, M Herrero; Gimenez, S; Vergara, J; Viles, E I Lladό; Martinez, H; Roca, G Rodríguez; Sánchez, L; Díaz, JA Muñoz; Frias, JF; Castaño, A; Jiménez, JJ Díaz; Rodríguez, Ά de Cossío; et al.
Abstract : Background: Osteoarthritis (OA) is the most prevalent joint disease and the leading cause of disability from 60 years onwards. In fact, 14, 8% of the Spanish population has OA. This study aimed to analyze the indications and average doses prescribed in the treatment of knee osteoarthritis in Primary Care in Spain. Objectives: This study aimed to analyze the comorbidity profile of men and women affected by symptomatic knee OA and the differences between genders in the perception of health status with regard to pain and loss of function due to their OA, quality of life and mental health. Methods: The EMARTRO study was designed as an observational, multicenter, transversal study to compare probability of suffering a comorbidities based on presence of symptomatic knee OA visited by GPs. Sociodemographic, anthropometric, clinical parameters and clinical variables of interest were recorded. The probability of suffering comorbidities based on presence OA was estimated using the Odds Ratio estimation with conditioned logistic regression models. Depending on the variable, comparisons between groups were done using t-Student, Chi-square and Mann-Whitney. Results: A total of 646 patients were included, 71% were women. Mean (SD) age was 67.9 (6.6) years. Patients were obese without gender differences, with a BMI of 30.4 (4.4) and 31.2 (5.5) (p=0.0651) in men and women, respectively. Men had a mean (SD) systolic blood pressure higher than women, 134.7 (15.0) vs 132.2 (14.5) mmHg (p=0.0453) and no differences were observed in diastolic pressure (p=0.5930). As regards to the concomitant pathologies, no increase was detected in the likelihood of suffering comorbidities linked to the gender [OR=0.607 (95% CI: 0.260–1.418) p=0.2490]. Men with OA were more likely to have angina pectoris [OR=4.493 (95% CI: 1.299–15.536) p=0.0176] and underwent coronary bypass [OR=3.706 (95% CI: 1.389–9.890) p=0089]. Osteoarthritic women elicited more pain in Huskisson's VAS 62.8 (14.7) vs 66.8 (15.4) mm (p=0.0027) and worse function according to the Lequesne index 10.0 (4.9) vs 12.1 (4.7) (p<0.0001). In terms of quality of life according to the EuroQol, women presented worse quality of life in dimesion of mobility (p=0.0001) and in the dimensions of daily activities, pain/discomfort and anxiety/depression (p<0.0001). Finally, regarding mental health status, women had worse scores in the Goldberg scale to detect psychological disorders (p<0.0001) and more cases of anxiety and depression according to the HAD scale (p<0.0001). Conclusions: The results of the present study indicate that women with osteoarthritis of the knee, despite having the same diagnosis and a similar comorbidity profile to men, have a worse perception of health status regarding the symptoms of their osteoarthritis, their quality of life and their mental health. Disclosure of Interest: M. Herrero Barbero Employee of: Bioiberica, S. Gimenez: None declared, J. Vergara: None declared, E. Viles I Lladό Employee of: Bioiberica, H. Martinez Employee of: Bioiberica, G. Rodríguez Roca: None declared, L. Sánchez Employee of: Bioiberica, J. A. Díaz Muñoz: None declared, J. F. Frias: None declared, A. Castaño: None declared, J. J. Jiménez Díaz: None declared, Ά. Rodríguez de Cossío: None declared, R. Belenguer: None declared, J. Vergés Milano Consultant for: Bioiberica, Employee of: Bioiberica, J. L. Llisterri: None declared